Stylistic devices describing faith in The novel ‘life of pi’ by yann martel and its vietnamese equivalent translated by trinh lu (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study attempted to investigate the stylistic devices used to describe faith in the novel “Life of Pi” and how they are translated into Vietnamese. The data for analysis was 120 samples (60 in Vietnamese and 60 in English) collected from the novel in two languages, English and Vietnamese. The research was carried out based on the combination of a variety of methods, namely qualitative, quantitative, descriptive and comparative. Data was collected, described, analyzed and compared to conclude the findings. The study found that among three categories used to describe faith, lexico-syntactical SDs are the most predominant ones, including climax, paradox and simile helping sentences deep in meaning. Coming to the second place is lexical SDs with hyperbole and especially metaphor which can sharpen their imaginations about faith. Lastly is syntactical SDs, including rhetorical question and repetition to lay emphasis for the topic. Thanks to those devices, Pi’s religious belief is linked closely to his spiritual growth, which makes the readers enjoy the wealth of the novel immensely. They also evokes the human imagination to think of the goodness and morality of people. As for translation method, literal translation is the dominant one and the translation procedures mostly are modulation, shift, cultural equivalent, descriptive equivalent as well as componential analysis, namely.